1979
DOI: 10.1021/j100470a012
|View full text |Cite
|
Sign up to set email alerts
|

Trapped and solvated electrons produced in ethanol glass in the presence of an applied electric field

Abstract: Optical absorption of e80f and ef produced in ethanol glass in the presence of an applied electric field decreased in intensity compared to that in the absence of the field. This is interpreted as due to a decreased rate of the transition for electrons from a delocalized state to a localized state. The wavelength dependence of the decrease is explained in terms of the density of states of phonons which is responsible for the electron-phonon coupling interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…18 The full power of this approach will, however, only be attained when considering changes in the optical response due to external influences,39 such as those recently observed in an applied electric field. 40 Considering the homologous series ROH (R = H, Me, Et, 1-Pr, 1-Bu, and 1-Oct), we see that the polarizability is highest in water, drops substantially for the solvated electron in methanol, increases slightly in ethanol, and remains fairly constant thereafter. The mean-squared radius of the excess charge distribution associated with the solvation site behaves very similarly.…”
Section: Discussionmentioning
confidence: 84%
“…18 The full power of this approach will, however, only be attained when considering changes in the optical response due to external influences,39 such as those recently observed in an applied electric field. 40 Considering the homologous series ROH (R = H, Me, Et, 1-Pr, 1-Bu, and 1-Oct), we see that the polarizability is highest in water, drops substantially for the solvated electron in methanol, increases slightly in ethanol, and remains fairly constant thereafter. The mean-squared radius of the excess charge distribution associated with the solvation site behaves very similarly.…”
Section: Discussionmentioning
confidence: 84%
“…It was also reported that high electrochemical energy of solvated electrons ( e aq − ) can enable difficult chemical reactions to happen 48 . Moreover, the presence of an external electric field or electromagnetic field can release the solvated electrons from their confined environment of surrounding molecules 49 . This is because e aq − in water has very small diffusion efficiency (4.8 × 10 −5 cm 2 /s) and electron mobility (1.84 × 10 −3 cm 2 /V · s) 50 .…”
Section: Resultsmentioning
confidence: 99%